2005
DOI: 10.1016/j.pain.2004.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Role of central and peripheral mGluR5 receptors in post-operative pain in rats

Abstract: Metabotropic glutamate receptors (mGluRs) have previously been shown to play a role in pain transmission during inflammatory or neuropathic pain states. However, the role of mGluR5 in post-operative pain remains to be fully investigated. The present study was conducted to characterize analgesic activity of 2-methyl-6-(phenylethynyl)-pyridine (MPEP) in the skin-incision-induced post-operative pain model in rats. MPEP is a potent and selective mGluR5 antagonist with high affinity (K(i)=6.3+/-0.9 nM) in rat corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…Finally, it has also been suggested that both peripheral and central mGluR5 receptors may play a role in nociceptive transmission observed during post-operative pain in rats (217). In this model, MPEP (ED 50 = 15 mg/kg, i.p.)…”
Section: Nociceptionmentioning
confidence: 95%
“…Finally, it has also been suggested that both peripheral and central mGluR5 receptors may play a role in nociceptive transmission observed during post-operative pain in rats (217). In this model, MPEP (ED 50 = 15 mg/kg, i.p.)…”
Section: Nociceptionmentioning
confidence: 95%
“…On the other hand, MPEP was found to be inactive in models of acute pain. In addition, systemic, local, and central application of MPEP was found to be efficacious in a model of postoperative pain in rats (Zhu et al, 2005), suggesting a role for both peripheral and central mGlu5 receptors in that condition. The early work on the role of mGlu5 receptors in chronic pain has been summarized by Slassi et al (2005) and seems to indicate that negative allosteric mGlu5 ALLOSTERIC MODULATION OF FAMILY C GPCRS receptor modulators are more effective in reversing thermal hyperalgesia compared with mechanical hyperalgesia or allodynia in both inflammatory and neuropathic pain models.…”
Section: A Allosteric Ligands For Group I Metabotropic Glutamate Recmentioning
confidence: 96%
“…Indeed, both spinal mGluR5 and TRPV1 have been demonstrated to contribute to pain hypersensitivity under pathological pain conditions (Caterina et al, 2000;Walker et al, 2001a;Zhu et al, 2005;Kanai et al, 2006). Whereas a functional role for mGluR5 in superficial dorsal horn neurons (i.e., postsynaptic neurons) has recently been demonstrated (Hu et al, 2007), relatively little is known about how presynaptic mGluR5 contributes to nociceptive synaptic transmissions in the spinal dorsal horn.…”
Section: Introductionmentioning
confidence: 99%